The influence of information technology on sustainable supply chain management: a multicase approach - Mantovani, Pedro Henrique Matos (2019)
Sustainability became a trend topic for business strategy, and companies are considering it as a central concern, enforcing activities that affect positively the environment and the society besides economic performance. Corporations began to speak on sustainability and invest resources to build internal capacity on sustainability due the increasing environmental stress, which generated risks and cost. This is already changing the competitive landscape, forcing companies to change their way of thinking about products, technologies, processes and business models. Companies invest on sustainability triggered by different reasons, like external pressures, seeking for economic performance, and environmental performance improvement. A company can achieve benefits by pursuing sustainable processes or sustainable products, projects regarding sustainable development influence the whole company, forcing companies to pursuit a sustainable supply chain. Collaboration between parties became essential for the generation of value and Information Technology is the main tool to allow collaboration, manage data, and promote the best practices; information systems are powerful enabling tools to respond social, cultural, and legislative pressures regarding sustainable concerns. The present study aims to understand at what level information technology leverage sustainable supply chain management performance. To analyze that, twelve qualitative interviews were conducted with IT, HRM and Supply Chain managers from seven different companies. Based on the multi-cases analysis this study provides evidence that information technology plays an extremely important role within the companies’ supply chains, generating positive results for the company, leveraging sustainable development. The main role of information technology relies on the integration of the companies' areas, orchestrating the processes, collecting and analyzing data. Finally is possible to infer that technology brings great performance gains in processes, especially on manufacturing and logistics area, optimizing resources, reducing errors and waste, in the short term, the impact of technology on the supply chain is most noticeable in the environmental sphere of sustainability. However, the analyzed companies have not yet reached a maximum degree of maturity in the process of digitalization, existing possibility to evolve in the use of technology to make smarter processes.